2002
DOI: 10.1002/ccd.10225
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mitral balloon valvuloplasty in pregnant women with mitral stenosis

Abstract: Forty-four consecutive pregnant patients with mitral stenosis were submitted to percutaneous mitral valvuloplasty (PMV) over a period of 12 years. The mean age was 28 +/- 6 years and the mean gestational age was 23 +/- 6 weeks. The mean mitral valve area had a significant increase from 1.17 +/- 0.26 to 2.06 +/- 0.41 cm(2) (P = 0.0000). The mean mitral valve gradient decreased from 16.22 +/- 5.55 to 7.94 +/- 3.75 mm Hg (P = 0.0001). The procedure was performed successfully in 95% of the patients and there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In current practice minimally invasive percutaneous mitral balloon valvuloplasty (PMBV) is the procedure of choice and has almost replaced the open surgical mitral valve commissurotomy 5 . Balloon mitral valvotomy has been observed to improve maternal and fetal outcome in severe MS during pregnancy1, 7, 8, 9, 10, 11. Even long term obstetric outcome and development of children born to these women has been found to be good 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In current practice minimally invasive percutaneous mitral balloon valvuloplasty (PMBV) is the procedure of choice and has almost replaced the open surgical mitral valve commissurotomy 5 . Balloon mitral valvotomy has been observed to improve maternal and fetal outcome in severe MS during pregnancy1, 7, 8, 9, 10, 11. Even long term obstetric outcome and development of children born to these women has been found to be good 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The recent reports by Mangione et al [10], Fawzy et al [11], and Lee et al [12] all confirmed that no developmental or growth abnormalities were found in children born of mothers who underwent percutaneous balloon mitral valvuloplasty during their gestation. The latest report by Nercolini et al [13] in this issue lends further support to this nonsurgical therapeutic approach.…”
mentioning
confidence: 62%
“…[ 12 ] Percutaneous mitral valvuloplasty should be considered if cardiac performance deteriorates. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%